Characterization of phonocardiogram signals using bispectral estimation - Ergen, B; Tatar, Y (Ieee, 2005)
The application of the bispectrum as a high-order spectrum (HOS) method in analyzing normal and pathological heart sound signal is investigated in this paper. The bispectrum of phonocardiograrn (PCG) signals is used to characterize the abnormalities while detecting non-linearity or non-Gaussianity in order to improve the diagnostic performance. In the comparison of the diagonal slice of the bispectrum and the power spectrum of PCG signal, the results have shown that the HOS reveal the differences in heart sound analysis indicating non-Gaussianity or non-linearity. It is concluded that the diagonal slice and the peaks of bispectrum are efficiently determine the cardiac dysfunctions effecting on heart sounds.
8th International Symposium on Signal Processing and Its Applications -- AUG 28-31, 2005 -- Sydney, AUSTRALIA
Keywords: high order spectrum; bispectrum; heart sounds; PCG